ECONOMIC AND LEGAL ASPECTS OF ORGANIZING MANAGEMENT IN UZBEKISTAN - Yuldasheva Saida Nematovna (Journal Park Publishing, 2025)
The transition of Uzbekistan from a centrally planned to a market-oriented economy has necessitated comprehensive reforms in the sphere of public and corporate management. This article explores the economic and legal aspects of organizing management in Uzbekistan by examining institutional frameworks, legal foundations, and administrative practices. Particular attention is paid to the development of corporate governance mechanisms, regulatory reforms, public sector efficiency, and the alignment of national practices with international standards. The article also highlights current challenges and forward-looking strategies aimed at improving transparency, accountability, and economic competitiveness through effective management.
Keywords: Uzbekistan, management organization, legal framework, economic reforms, corporate governance, institutional development, administrative regulation, economic transition.